2022
DOI: 10.3389/fimmu.2022.1005067
|View full text |Cite
|
Sign up to set email alerts
|

Glial receptor PLXNB2 regulates schizophrenia-related stress perception via the amygdala

Abstract: Stress is a trigger for the development of psychiatric disorders. However, how stress trait differs in schizophrenia patients is still unclear. Stress also induces and exacerbates immune activation in psychiatric disorders. Plexins (Plxn) and its ligands semaphorins (Sema) are important cellular receptors with plural functions in both the brain and the immune system. Recently, the role of Plxn/Sema in regulation of neuroinflammation was also noticed. Here, when investigating immune mechanisms underlying stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…The authors concluded that Plexin‐B2 has a role in schizophrenia‐related stress via glial signaling in the amygdala. More generally, this work provides links among Plexin‐B2, response to psychological stress, and inflammation 43,48 …”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…The authors concluded that Plexin‐B2 has a role in schizophrenia‐related stress via glial signaling in the amygdala. More generally, this work provides links among Plexin‐B2, response to psychological stress, and inflammation 43,48 …”
Section: Resultsmentioning
confidence: 92%
“…Plexin-B2 interaction with Sema4A and Sema4B in the amygdala impacts stress responses via a very different mechanism. 48 Plexin-B2, response to psychological stress, and inflammation. 43,48 Plexin-B2 interactions with Semas play important roles in motility and neuronal guidance during development and they regulate dendritic arborization and spine density after birth.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations